Sustainability education in chemistry - Tolppanen, Sakari (LUMAT-B: International Journal on Math, Science and Technology Education, 2016)
Education for sustainable development (ESD), or sustainability education, should be an important part of education, especially chemistry education. However, sustainability education presents new challenges to education, as the teacher needs to find new ways to deal with multidisciplinary issues and the emotions it evokes. This article presents some of the challenges of sustainability education and gives guidelines on how to overcome these challenges. The article is based on a PhD thesis, by Sakari Tolppanen. In the thesis, students’ questions, actions and expectations for sustainability education were studied. Watch video to see video preview: https://youtu.be/6SmxHMOEVno